Self-Control of Special Children: An Exploratory Study of Physically Handicapped - Jahan Ara Shams, Safia Janjua. Muhammad Zafar Iqbal (JIE, 2024)
The Purpose of this study was to explore the nature of Self-Control (SC) among special children which were physically handicapped. The study was qualitative in nature. Participants of the research were 15 special children (10 boys and 5 girls). The context of the study was Mirpur AJK, Pakistan.